(untitled) (Journal of actual problems of jurisprudence, 2016)
Public consciousness in conditions of social-economic relations and the questions of influence public consciousness of the people of existing social life, changes and development of individual consciousness of people from the point of legal science, ideological and political foundations of a new national idea are considered in the article.